Effect of tofacitinib treatment on active MRI sacroiliitis in psoriatic arthritis patients - E. E. Gubar; Yu. L. Korsakova; E. Yu. Loginova; A. V. Smirnov; S. I. Glukhova; T. V. Korotaeva (Научно-практическая ревматология)
Axial involvement in psoriatic arthritis is quite common. There is no data on the use of tofacitinib, an oral Janus kinase inhibitor, in psoriatic arthritis patients with axial involvement, nor is there any data on its effect on active MRI sacroiliitis.The aim of the study was to assess the effect of tofacitinib therapy on the dynamics of active MRI sacroiliitis in psoriatic arthritis patients.Materials and methods. 41 patients with active psoriatic arthritis fulfilling the CASPAR criteria were included. Median age was 41.0 [34; 50] years old, median disease duration was 6.0 [3; 10] years. Apart from a standard clinical examination, 40 patients underwent sacroiliac joint MRI on scanner Siemens General Electric 1.5 TESLA. Bone marrow edema on MRI (STIR) with one lesion on two consecutive slices or at least two lesions on a single slice, was considered active MRI sacroiliitis. Tofacitinib was given in 5 mg tablets twice a day with a possible dose increase up to 10 mg twice a day after 12 weeks of therapy. At the end of study, over a period of 24 weeks, sacroiliac joint MRI examination was repeated in 35 patients.Results. Prior to tofacitinib therapy, active MRI sacroiliitis was detected in 14 of 40 (35%) patients: bilateral – in 9 patients, unilateral – in 5 patients. At the end of 24 weeks therapy, active MRI sacroiliitis was detected in 4 of 35 (11.4%) patients observed: in 1 patient with baseline bilateral MRI sacroiliitis and in 2 patients with unilateral MRI sacroiliitis. 1 patient showed negative dynamics, that is, development of active MRI sacroiliitis (absent at baseline). The decrease in number of active MRI sacroiliitis patients is statistically significant (p=0.017). At baseline, inflammatory changes were detected in 23 of 80 (28.8%) sacroiliac joints, after 24 weeks of therapy they were found in 5 of 70 (7.1%; p=0.001) sacroiliac joints observed. During the treatment period, there was a significant decrease in the initially high activity of spondylitis. After 24 weeks of treatment, median BASDAI decreased from 6.0 [4.2; 7.0] to 1.4 [0.6; 3.2], median ASDAS-CRP from 3.8 [2.8; 4.4] to 1.5 [1.0; 2.1] (p=0.001 for both comparisons). Prior to tofacitinib therapy, high activity according to BASDAI was observed in 90.2% of patients, low activity – in 9.8%; at the end of study – in 13.5% and 86.5% of patients, respectively (p=0.001). At baseline, very high activity by ASDAS-CRP was detected in 61% of patients, high activity – in 29.2%, low activity – in 9.8% of patients. At the end of study there weren’t any patients with very high activity by ASDAS-CRP (p=0.001), high activity remained in 23.1%, moderate and low activity – in 30.7% and 46.2% of patients, respectively (p=0.001 for both comparisons). Significant differences between baseline symptoms in patients with MRI sacroiliitis and without it were defined by number of digits with dactylitis – 2 [0; 4] and 0 [0; 2] (p=0.04) and by ESR values – 47 [26; 76] and 20 [6; 37] mm/h (p=0.02). These parameters were higher in MRI sacroiliitis subgroup. By the end of study, these differences leveled out: the number of digits with dactylitis decreased to 0 [0; 0] and 0 [0; 0] (р=0.48), ESR – to 12 [6; 16] and 8 [6; 16] mm/h, respectively (p=0.78).Conclusion. Tofacitinib therapy shows high efficacy in reducing active MRI sacroiliitis and decreasing activity of axial involvement in psoriatic arthritis patients. The use of tofacitinib in patients with active MRI sacroiliitis as well as dactylitis and increased ESR levels demonstrated its high efficacy.